Cost effective thermoelectric composites from recycled carbon fibre: From waste to energy - Jagadish P.R.; Khalid M.; Li L.P.; Hajibeigy M.T.; Amin N.; Walvekar R.; Chan A. (Elsevier Ltd, 2023)
Bismuth compounds; Coated materials; Cost effectiveness; Energy harvesting; Fillers; Recycling; Sulfur compounds; Thermodynamic stability; Thermoelectricity; Waste heat; Bismuth telluride; Energy; Filler concentration; Low-grade waste heat; Recycled carbon fibres; Thermo-Electric materials; Thermoelectric composite; Waste to energy; Carbon fibers